The Outcomes of Gestational Diabetes Mellitus after a Telecare Approach Are Not Inferior to Traditional Outpatient Clinic Visits - Natalia Pérez-Ferre; Mercedes Galindo; M. Dolores Fernández; Victoria Velasco; Isabelle Runkle; M. José de la Cruz; Patricia Martín Rojas-Marcos; Laura del Valle; Alfonso L. Calle-Pascual (International Journal of Endocrinology)
Objective. To evaluate the feasibility of a telemedicine system based on Internet and a short message service in pregnancy and its influence on delivery and neonatal outcomes of women with gestational diabetes mellitus (GDM). Methods. 100 women diagnosed of GDM were randomized into two parallel groups, a control group based on traditional face-to-face outpatient clinic visits and an intervention group, which was provided with a Telemedicine system for the transmission of capillary glucose data and short text messages with weekly professional feedback. 97 women completed the study (48/49, resp.). Main Outcomes Measured. The percentage of women achieving HbA1c values <5.8%, normal vaginal delivery and having a large for-gestational-age newborn were evaluated. Results. Despite a significant reduction in outpatient clinic visits in the experimental group, particularly in insulin-treated women (2.4 versus 4.6 hours per insulin-treated woman resp.; P<.001), no significant differences were found between the experimental and traditional groups regarding HbA1c levels (all women had HbA1c <5.8% during pregnancy), normal vaginal delivery (40.8% versus 54.2%, resp.; P>.05) and large-for-gestational-age newborns (6.1% versus 8.3%, resp.; P>.05). Conclusions. The system significantly reduces the need for outpatient clinic visits and achieves similar pregnancy, delivery, and newborn outcomes.